Preparative enrichment and purification of nevadensin from Lysionotus pauciflorus using macroporous resins. Issue 2 (22nd January 2016) - Wen, Yaya; Du, Hongjian; Tu, Yanbei; Luo, Wei; Li, Qin; Zhu, Chao; Li, Yanfang; Liang, Bing
Abstract: An efficient method using macroporous adsorption resins for preparative enrichment and purification of nevadensin from Lysionotus pauciflorus Maxim was developed. The results indicated that non-polar HPD-100 resin offered the best adsorption and desorption performance, its adsorption data were well-fitted to the Freundlich isotherm and the pseudo-second-order kinetics model. Dynamic adsorption and desorption experiments have been investigated for optimization of chromatographic parameters. Through one cycle of dynamic adsorption/desorption, the purity of nevadensin in the extract, increased about 8.82-fold from 8.58% to 75.70%, with a recovery yield of 69.90%. The results suggested that HPD-100 resin can separate nevadensin effectively from plant material.